A Functional and Structural Study of Troponin C Mutations Related to Hypertrophic Cardiomyopathy - Pinto, Jose Renato (American Society for Biochemistry and Molecular Biology, 2009)
Recently four new hypertrophic cardiomyopathy mutations in cardiac troponin C (cTnC) (A8V, C84Y, E134D, and D145E) were reported, and their effects on the Ca(2+) sensitivity of force development were evaluated (Landstrom, A. P., Parvatiyar, M. S., Pinto, J. R., Marquardt, M. L., Bos, J. M., Tester, D. J., Ommen, S. R., Potter, J. D., and Ackerman, M. J. (2008) J. Mol. Cell. Cardiol. 45, 281–288). We performed actomyosin ATPase and spectroscopic solution studies to investigate the molecular properties of these mutations. Actomyosin ATPase activity was measured as a function of [Ca(2+)] utilizing reconstituted thin filaments (TFs) with 50% mutant and 50% wild type (WT) and 100% mutant cardiac troponin (cTn) complexes: A8V, C84Y, and D145E increased the Ca(2+) sensitivity with only A8V demonstrating lowered Ca(2+) sensitization at the 50% ratio when compared with 100%; E134D was the same as WT at both ratios. Of these four mutants, only D145E showed increased ATPase activation in the presence of Ca(2+). None of the mutants affected ATPase inhibition or the binding of cTn to the TF measured by co-sedimentation. Only D145E increased the Ca(2+) affinity of site II measured by 2-(4′-(2″-iodoacetamido)phenyl)aminonaphthalene-6-sulfonic acid fluorescence in isolated cTnC or the cTn complex. In the presence of the TF, only A8V was further sensitized to Ca(2+). Circular dichroism measurements in different metal-bound states of the isolated cTnCs showed changes in the secondary structure of A8V, C84Y, and D145E, whereas E134D was the same as WT. PyMol modeling of each cTnC mutant within the cTn complex revealed potential for local changes in the tertiary structure of A8V, C84Y, and D145E. Our results indicate that 1) three of the hypertrophic cardiomyopathy cTnC mutants increased the Ca(2+) sensitivity of the myofilament; 2) the effects of the mutations on the Ca(2+) affinity of isolated cTnC, cTn, and TF are not sufficient to explain the large Ca(2+) sensitivity changes seen in reconstituted and fiber assays; and 3) changes in the secondary structure of the cTnC mutants may contribute to modified protein-protein interactions along the sarcomere lattice disrupting the coupling between the cross-bridge and Ca(2+) binding to cTnC.